2022
DOI: 10.3390/ijms23168999
|View full text |Cite
|
Sign up to set email alerts
|

The Link between Gut Microbiota and Hepatic Encephalopathy

Abstract: Hepatic encephalopathy (HE) is a serious complication of cirrhosis that causes neuropsychiatric problems, such as cognitive dysfunction and movement disorders. The link between the microbiota and the host plays a key role in the pathogenesis of HE. The link between the gut microbiome and disease can be positively utilized not only in the diagnosis area of HE but also in the treatment area. Probiotics and prebiotics aim to resolve gut dysbiosis and increase beneficial microbial taxa, while fecal microbiota tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 133 publications
1
10
0
2
Order By: Relevance
“…The intestinal microbiome seems to be of central importance in the progression of HE [106,107]. The decreased expression of tight junction proteins and the increased BBB permeabilization have been addressed in the brain of germ-free mice compared with normal gut flora [108].…”
Section: Altered Gut Microbial Metabolites and Molecules May Disrupt ...mentioning
confidence: 99%
“…The intestinal microbiome seems to be of central importance in the progression of HE [106,107]. The decreased expression of tight junction proteins and the increased BBB permeabilization have been addressed in the brain of germ-free mice compared with normal gut flora [108].…”
Section: Altered Gut Microbial Metabolites and Molecules May Disrupt ...mentioning
confidence: 99%
“…Wirkung gegen intestinale grampositive und gramnegative Organismen, was sowohl Aerobier als auch Anaerobier einschließt. Klare Aussagen zu einer möglichen positiven Beeinflussung des Darmmikrobioms unter Rifaximin beim Menschen sind aufgrund der begrenzten Datenlage bei HE nicht möglich [16]. Für den primären Einsatz von Rifaximin bei einer oHE gibt es keine Leitlinienempfehlung und keine Arzneimittelzulassung in Europa und den USA [1,2].…”
Section: Rifaximin Hat Ein Breites Antimikrobielles Spektrum Mitunclassified
“…Gut microbiota plays an important role in regulating host physiological processes (e.g., immunity and metabolism), and its ecological disorders are closely related to the brain, liver and other organs ( Gonzalez-Ochoa et al, 2017 ; Tooley, 2020 ; Gabanyi et al, 2022 ). Recently, increasing medical studies reported that the gut-liver-brain axis plays a fundamental role in the pathogenesis of various diseases ( Won et al, 2022 ), which is the bidirectional relationship between the gut and its microbiota, the liver, and the brain. Besides, gut microbiota exert their actions at different levels of the gut-liver-brain axis, impacting disease progression via changing gut-liver-brain axis communication ( Fuenzalida et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%